Studi Penggunaan Natrium Bikarbonat pada Pasien Penyakit Ginjal Kronik dengan Asidosis Metabolik - Andilusia, Sindy; Hasmono, Didik; Kusumaningtyas, Atika Putri; Syifa', Nailis (LPPM Sekolah Tinggi Ilmu Farmasi Nusaputera, 2024)
Chronic Kidney Disease (CKD) is defined as a condition in which there are abnormalities in kidney performance, and occurs for at least 3 months. Metabolic acidosis is a disturbance of acid-base balance resulting in a decrease in plasma sodium bicarbonate concentration with a decrease in blood pH. Metabolic acidosis patients are characterized by (arterial pH <7.35, PCO2 <35 mmHg, and HCO3- <22 mEq/L [mmol/L]). Sodium bicarbonate increases plasma bicarbonate, and increases blood pH. This study aims to identify the pattern of sodium bicarbonate use in CKD patients who experience metabolic acidosis including type, dose, route, interval, and duration of drug administration at Universitas Muhammadiyah Malang Hospital. This study was conducted in the form of observational research by analyzing descriptively and retrospectively collecting data using Health Record data of patients who underwent hospitalization in the period 01 January 2022 – 31 December 2022. Based on the research that has been carried out, it is concluded that patients who meet the therapeutic targets are 23 patients (96%), indicated by the pattern of sodium bicarbonate use only used singly in all CKD patients with metabolic acidosis as many as 24 patients (100%), the most dose is (3x500mg) po as many as 20 patients (83%), with a duration of administration ≤ 5 days as many as 19 patients (79%). The suggestions that researchers convey are research that has been carried out, can be used as a reference and further guidance.